ANGLE RECESSION, THE SEQUELA OF EIGHT-BALL HYPHEMA AFTER SPRAYED BY FIRE HYDRANT: A CASE REPORT: Poster Presentation - Case Report - Resident - Nurwasis; Asti, Annisa Kinanti; Komaratih, Evelyn; Primitasari, Yulia (Majalah Oftalmologi Indonesia, 2023)
Introduction : Hyphema results from damage to the blood vessels of the iris or anterior ciliary body after blunt trauma, and in 56–100% of cases can occur angle recession. Case Illustration : A 40-year-old man complaints of pain and blurred left eye after being sprayed by a high-pressure fire hydrant five hours before coming to the emergency room. Visual acuity was 20/20 and hand movement in right and left eye, IOP is 13 mmHg and 18 mmHg in both eyes. Subconjunctival bleeding, conjunctival and pericorneal injections were found with punctate fluorescein test in the left eye. The cornea was edema and the anterior chamber was full of hyphema. Five days after being hospitalized and treated with topical atropine, antibiotics, and steroid in combination with oral tranexamic acid, the visual acuity was 5/6.5 and the hyphema was resolved. The IOP elevated after 1-6 weeks of follow-up in the outpatient clinic then timolol eyedrops were given. Gonioscopy showed widening of CBB, torn iris processus 2 clock hours in the inferior quadrant. The antiglaucoma medication was stopped due to the controlled IOP in the end episode of the treatment. Discussion : Angle recession involves a tear between the longitudinal and circular muscle fibres of the ciliary body. Medication is needed to control the IOP, while surgical management only indicated in cases where medical treatment fails to control the IOP and risk of progressive visual loss. Conclusion : Angle recession can occur after blunt eye trauma with hyphema and IOP control is needed to prevent the development of secondary glaucoma.